Development of the Mind-Body-Spiritual (MBS) Nursing Care Model for Coronary Heart Disease Patients - Ninuk Dian Kurniawati; Nursalam Nursalam; Suharto Suharto (Universitas Airlangga, 2018)
Introduction: Patients with coronary heart disease (CHD) may experience various physical, psychological or spiritual issues. A holistic mind-body spiritual nursing care (MBS) model is needed to help patients' cope with the issues. This study aimed to develop an MBS nursing care model for CHD patients.Method: The study employed a crossectional design with 110 CHD patients participated in the study. Respondents were asked to fill out questionnaires to gather the required data. Criteria for respondent selection were Moslem, aged 40-75 year, medical diagnosis of CHD, and haemodynamically stable. The independent variables were focal, contextual and residual stimuli, while the dependent variables were coping and spirituality. Data were analyzed using partial least square.Results: The results show that the mind-body-spiritual nursing care formed focal stimuli. Spirituality is formed by focal, contextual, residual stimuli and coping style. Nursing care significantly affects spirituality, shown by T-statistics of 6.795. Spirituality can be explained by patience, endeavour toward wellness, and offer the results only to God by 72%, while the rest is explained by other factors.Conclusion: MBS nursing care model has a strong relationship with spirituality. This model needs to be applied in a further research to see its effectiveness in improving spirituality and expression of cardiovascular risk inflammatory markers.